On the environmental effects on a point discharger (2011)
The environmental effect on a point discharger has been investigated. It was found that the magnitude of point-discharge current (Ip) measured from a discharger is strongly affected by the presence of other dischargers, particularly when they are very close to the discharger through which Ip is measured. The starting potential depends on the tip clearance of the central discharger rather than the separation of the points. At higher tip clearances the compound discharger exhibits a stepped-leader like process. Atmospheric contaminants also affect the magnitude of Ip.